BUCCAL FAT PAD AS A PEDICLED AUTOGRAFT FOR ROOT COVERAGE: A CASE REPORT - JATIN CHAUHAN; RAJESH KUMAR THAKUR; BIPIN KUMAR YADAV; DIKSHA GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
The buccal fat represents a specialized and organized adipose tissue that maintains its volume and stability over long periods of time and serves as a well-vascularized, easily accessible local flap for reconstructive procedures such as the enhancement of root coverage in severe recession defects, thereby augmenting the dimensions of keratinized mucosa. Areas with Miller's Class III and IV gingival recessions are not considered amenable to intervention utilizing surgical root coverage methodologies because of the poor prognosis with existing techniques. In this case report, a pedicled buccal fat pad (PBFP) was used as a subepithelial grafting technique for root coverage in a maxillary posterior tooth exhibiting a Class III gingival recession defect coupled with a deficiency of keratinized gingiva. At a 3-month follow-up, this approach demonstrated effective root coverage, increased keratinized tissue, and improved patient comfort, as documented, with no notable complications.